Plasmid-Coded Linezolid Resistance in Methicillin-Resistant Staphylococcus aureus from Food and Livestock in Germany - Tobias Lienen; Mirjam Grobbel; Bernd-Alois Tenhagen; Sven Maurischat (MDPI AG, 2022)
Resistance of methicillin-resistant Staphylococcus aureus (MRSA) from food and livestock to last resort antibiotics such as linezolid is highly concerning, since treatment options for infections in humans might be diminished. Known mechanisms of linezolid resistance include point mutations in the 23S rRNA gene and in the ribosomal proteins L3, L4 and L22 as well as an acquisition of the cfr, optrA or poxtA gene. The objective of our study was to characterize antimicrobial resistance (AMR) determinants and phylogenetic relationships among linezolid-resistant (LR-) MRSA from food and livestock. In total, from more than 4000 incoming isolates in the years 2012 to 2021, only two strains from 2015 originating from pig samples exhibited linezolid resistance in the antimicrobial susceptibility testing with MICs of ≥8 mg/L. These LR-MRSA were characterized in detail by whole-genome sequencing and phylogenetic analyses using cgMLST. The LR-MRSA strains showed resistances to ten and eight different antibiotics, respectively. Both strains harbored plasmid-coded cfr genes mediating the linezolid resistance. The cfr genes showed identical sequences in both strains. In addition to the cfr gene, genes for phenicol and clindamycin resistance were detected on the respective plasmids, opening the possibility for a co-selection. The LR-MRSA differed distantly in the phylogenetic analyses and also to other MRSA from pig samples in the year 2015. In conclusion, the occurrence of LR-MRSA in food and livestock seems to be very rare in Germany. However, carriage of plasmids with linezolid resistance determinants could lead to further linezolid-resistant strains by horizontal gene transfer.